Real Business Cycle: Stochastic driving force decomposition of output dynamics in East Java - Rofik, Mochamad; Dwidyah Rini, Ayu; Kaluge, David; Alfarado, Rafael (Faculty of Economics and Business, University of Muhammadiyah Malang, 2023)
This study aims to examine output dynamics in East Java using the Real Business Cycle (RBC) model. We constructed an RBC model with two stochastic shocks originating from the demand and supply sides. The RBC model in this study shows that output dynamics, as the driver of the business cycle in East Java, are mostly caused by exogenous shocks originating from the demand side. The model also shows that some variables such as wage levels, consumption, and capital accumulation exhibit inertia patterns in response to shocks. Therefore, after releasing the assumptions underlying the RBC model and accommodating fiscal and monetary policies, we argue that the response time lag shown by some of these variables can be advantageous for authorities to mitigate the impact of shocks and determine policies. Additionally, two main factors that determine policy effectiveness are understanding the sources of shocks and the timing of policy implementation.